Small Molecules Incorporating Privileged Amidine Moiety as Potential Hits Combating Antibiotic-Resistant Bacteria - Selwan M. El-Sayed; Samar A. Ahmed; Kanika Gulia; Justin R. Lenhard; Ahmed H.E. Hassan; Abdelbasset A. Farahat (MDPI AG, 2023)
The continuing need for the discovery of potent antibacterial agents against antibiotic-resistant pathogens is the driving force for many researchers to design and develop such agents. Herein, we report the design, synthesis, and biological evaluation of amidine derivatives as new antibacterial agents. Compound 13d was the most active in this study against a wide range of antibiotic-resistant, and susceptible, Gram-positive, and Gram-negative bacterial strains. Time-kill assay experiments indicated that compound 13d was an effective bactericidal compound against the tested organisms at the log-phase of bacterial growth. Docking simulations were performed to assess in silico its mode of action regarding UPPS, KARI, and DNA as potential bacterial targets. Results unveiled the importance of structural features of compound 13d in its biological activity including central thiophene ring equipped with left and right pyrrolo[2,3-b]pyridine and phenyl moieties and two terminal amidines cyclized into 4,5-dihydro-1H-imidazol-2-yl functionalities. Collectively, compound 13d represents a possible hit for future development of potent antibacterial agents.